First record of Caprella mutica from the Iberian Peninsula: expansion southwards in European waters. (2014) - Almón, B.; Pérez, J.; Bañón, R.; Trigo, J.
Abstract : The caprellid amphipod, Caprella mutica, is a well-known invasive species, originating in the Sea of Japan, which has been rapidly expanding along the coasts of North America, Europe and Oceania for the last forty years. Caprella mutica is frequently associated with man-made structures, especially those dedicated to aquaculture activities, where it can reach high densities of up to 300, 000 ind./m 2 . A well-established population of C. mutica was recently found by SCUBA-divers in Galician waters (north-west Spain) at 6 different man-made floating structures along Ría de Arousa. The record of this species in this location implies a new southernmost limit of distribution, extending the known distribution range in Atlantic European waters and confirming the continuity of the colonization southwards.